Nonvolatile Programmable WSe2 Photodetector. Issue 12 (13th April 2020) - Molina‐Mendoza, Aday J.; Paur, Matthias; Mueller, Thomas
Abstract: Optoelectronic devices with nonvolatile memory are an important component in a wide variety of applications ranging from optoelectronic random‐access‐memories, with the advantage of using optical stimuli as an added parameter, to complex artificial neuromorphic networks that pretend to mimic the working schemes of the human brain. In the past few years, 2D materials have been proposed as attractive candidates to build such optoelectronic devices with memory due to their excellent optoelectronic properties and high sensitivity to external electric fields. Here, a WSe2 monolayer p–n junction working as a nonvolatile programmable photodetector is reported, that, enabled by a split‐gate configuration with embedded charge‐trapping layers, is capable of retaining custom responsivity values over time, prior configuration by the user. Once configured, this photodetector can operate without external applied bias voltage as a self‐driven photodetector, as well as without external back‐gate voltage thanks to the charge stored in the floating gates. Furthermore, the device shows a remarkable performance, with open‐circuit voltage around 1 V at approximately 270 W m −2 white light, fill factor higher than 30%, and fast response times. This programmable photodetector sets a new concept as a building block in more complex image‐sensing systems. Abstract : A monolayer WSe2 photodetector based on a split‐gate configuration, including a charge‐trapping layer embedded in the insulator, is demonstrated. The split‐gates allow programming the device to any desired responsivity value, and the floating gates serve to retain the preconfigured settings over long periods. Once programmed, the device operates in short‐circuit current (zero bias voltage) and without external gate‐voltages.